Synthesis and characterization of mesoporous carbon through inexpensive mesoporous silica as template - Karandikar, Prashant R.; Patil, K. R.; Mitra, A.; Kakade, Bhalchandra A.; Chandwadkar, Asha J. (Microporous and Mesoporous Materials, 2007)
Mesoporous silica materials have been synthesized through sol-gel reaction using inexpensive sodium silicate as source of silica and low cost hydroxy carboxylic acid compounds as templates/pore forming agents. The material measured surface area of 1014 m(2)/g, pore diameter of 65 angstrom and pore volume of 1.4 cc/g when parameters like time and temperature of synthesis along with mole ratio of TA/SiO(2) were optimized. Here TA stands for tartaric acid. Carbonization of sucrose inside the pores of above silica material at 900 degrees C followed by removal of silica framework using aqueous ethanoic solution of NaOH gave rise to mesoporous carbon material. The resulting materials were characterized by N(2)-sorption, FTIR spectroscopy, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, thermal analysis and cyclic voltammetry. Three dimensional interconnecting wormhole channel arrangement of mesoporous silica template leads to mesoporous carbon replica with surface area of 1200 m(2)/g. X-ray photoelectron spectroscopic study (XPS) of the mesoporous carbon material shows the concentration of carbon atom in the range of 97-98% with 1-2% oxygen and negligible amount of silica. The electrochemical double layer capacitance behavior of carbon material with the specific capacitance value of 88.0 F/g at the scan rate of 1 mV/s appears to be promising. (C) 2006 Elsevier Inc. All rights reserved.
Keywords: Electrochemical properties; hydroxy carboxylic acid; mesoporous carbon; Mesoporous silica; sodium silicate